The racing game. Vol. 2 [videorecording (DVD)] - Mackenzie, John, 1928-2011; Bucksey, Colin, 1946-; Duffell, Peter; Gwilym, Mike; Ford, Mick, 1957-; Francis, Dick (Distributed by Acorn Media, 2008)
Steeplechase rider turned private detective Sid Halley returns to the track to investigate all manner of misdeeds, from conniving bookies and blackmail to murder. Dick Francis fans will delight in this mystery series. Includes biography of Dick Francis.